Uganda's experience with debt and economic growth: An empirical analysis of the effect of public debt on economic growth : 1980-2016 - Richard Ssempala; Kurayish Ssebulime; Enoch Twinoburyo (Journal of Economic Structures, 2020)
Background: Empirical evidence on the effect of public debt on the economic growth of a country remains ambiguous. No theoretical convergence on the respective nexus has been attained. For the case of Uganda in particular, the public debt question remains critical in the country's development trajectory. Under the Highly Indebted Poor Countries (HIPCs) initiative, Uganda was the first country to receive a debt relief of worth US650 million in the 1990s and later in 2006, under the Multilateral Debt Relief Initiative (MDRI), the country generously received 100% debt forgiveness/cancelation which consequently reduced the stock of country's debt to 1.6 billion. However, of recent, the debt stock has kept on increasing from UGX 14.257 trillion (5.5 billion) in 2000 to the current UGX 35.3 trillion (9.8b) in July 2017 and it is projected to continue increasing in the short to medium term given the robust NDPII core projects and priorities which are set to attract more borrowing. The study employs the Auto Regressive Distributed Lag (ARDL)-bounds testing approach which is superior and suitable for our small sample. Results: The results reveal that public debt has a significant negative impact on economic growth in short run whereas in long-run debt has a mixed impact on Uganda's economy. The total debt service has a negative impact whereas Gross debt as a share of GDP has a positive impact on the economy. The findings also reveal that Public debt has a negative effect on Uganda's economic growth in the short run. The impact is however found to be positive in the long run. This result is in line with the study expectations and some findings by earlier researchers who found a negative impact of public debt on GDP and investment. The results suggest that the current trend of Uganda's borrowing is to continue constraining the resources in the short run. Conclusion: The conclusion of the study in view of emerging findings especially on debt, various policy implications have emerged. At the current rate of borrowing, Uganda is likely to have deteriorating economic growth partly because such public borrowing adversely affects investment. The study thus recommends for policies geared toward efficient use of borrowed funds especially for such projects that have high potential to unlock the production capabilities of the country. There is a need for the government of Uganda to institute mechanisms to ensure efficient use of borrowed funds.
Keywords: 330; Auto-Regressive Distributed Lag (ARDL); Debt relief; Spurious results; Co-integration